A CASE OF PRIMARY CONGENITAL LYMPHEDEMA - SHANTHI RAMESH,; MOHAMED YASEEN SAIT,; SURESH KIRUPANANTHAN,; RAASHIDHA SUBRAMANIYAN,; VIDHYA THANGAKUMAR,; DIVYA MURALI,; GANAPATHY, (International Journal of Pharma and Bio Sciences, 2014)
Primary congenital lymphedema is a rare disorder of childhood which presents from birth and progresses into late childhood. It can be either unilateral or bilateral. Here we are presenting an eight year old boy with primary congenital lymphedema who was referred to us with progressive non-pitting edema of left lower limb since birth. The purpose of presenting this case is its rarity.